Platelet Rich Plasma for Regenerative Medicine Treatment of Bovine Ovarian Hypofunction - Cremonesi, Fausto; Bonfanti, Stefano; Idda, Antonella; Lange-Consiglio, Anna (Frontiers in Veterinary Science, 2020)
Recent studies on cull cows have shown that ovarian abnormalities, particularly ovarian insufficiency, are a common cause of reproductive failure. The aim of this study was to treat bovine ovarian failure with intraovarian administration of autologous platelet rich plasma (PRP), which is rich in growth factors, chemokines and cytokines, that could stimulate follicular growth and steroidogenesis. Twelve cows with ovarian hypofunction were enrolled in the study and theywere randomly allocated in control group (CTR) and treated group (six animal for group). In the treated group, only five animals received the PRP treatment because intraovarian administration was hindered in one by a rectovaginal fistula. Animals of control group were treated by intraovarian administration of physiological solution. In the 4 weeks after PRP injection, a mild to strong increase in progesterone (PRG) concentrations was detected in four of the five cows treated. Artificial insemination (AI) resulted in four pregnancies that are still ongoing (7th month). Intraovarian administration of PRP improved ovarian function after two months of treatment. This effect may be due to reduction of follicular atresia or to revitalization of dormant oocytes allowing restoration of fertility.